Gerakan Dakwah Jama'ah Tabligh di Kalangan Wanita dalam Pembinaan Keluarga Muslim - Muhamad Bisri Mustofa (Mau'idhoh Hasanah, 2019)
Abstract Jama'ah Tabligh is a missionary movement that has the concept of movement with the method of da'wah and tabligh. The characteristics of the Jama'ah Tabligh propagation movement are: pure and authentic (dzâtiyyâh), which is authentic as God's calling, encouraging progress (taqaddûmîyah), namely progress that continues to uphold morality, universal values ​​(shamîlâhi) covering all aspects of life, integrating progress three systems of life (manhaj al hayat), emphasizing the principles of the sublime religion and distancing themselves from the differences of the schools. In connection with the above statement, the author would like to know the Tablighi Jama'ah movement among women in fostering Muslim families spearheaded by women who have been Khurûj with their husbands, then what about affection for their families especially children left behind, and liability obligations for families who left. Because on the other hand he also has to carry out his duties as a parent as it should be, including giving love to children, educational guidance, religion towards children and spiritual and physical support for children left by their parents when Khurûj. The issue to be investigated is how is the Tablighi Jama'ah movement among women in developing Muslim families? What material is the da'wah used by the Tablighi Jama'ah in fostering Muslim families? And what are the obstacles to the Tablighi Jama'ah movement in fostering Muslim families? The purpose of this study was to determine the character of the Tablighi Jama'ah movement among women in family formation, find out the material used, and find out the constraints of the Jama'ah Tabligh propaganda movement in the formation of Muslim families. This study seeks to provide an interpretation of the phenomena of the Tablighi Jama'ah, of course in accordance with the predetermined research focus and also uses relevant theories to be able to uncover the propaganda movement of the Tablighi Jama'ah among women in fostering Muslim families. The theory is a functional structural theory, family theory and family according to Islamic teachings.